Patterns of Distribution of Bivalve Populations in a Mediterranean Temporary River - Gama, M. (2020)
In the south of the Iberian Peninsula, many rivers are intermittent, a state most likely to be exacerbated by climate change, strongly affecting river biota. An additional challenge for native biota in this area is the arrival of new species, frequently aided by humans, and bivalves are particularly at risk. Here we assessed whether the native (Unio delphinus) and invasive (Corbicula fluminea) bivalves differed in habitat use. To address this question, we sampled populations of both species in six isolated permanent pools in the same river during summer in three consecutive years. U. delphinus occurred in all pools, while C. fluminea occurred only in the two most downstream pools. U. delphinus, but not C. fluminea, was found preferentially in patches under riparian vegetation cover. Both species were found in similar sediment types (coarse and fine gravel respectively). Although U. delphinus was present in all pools, recruitment was detected only in 2016, in one pool. We concluded that both species have the potential to compete for space, but a well-developed riparian vegetation cover may provide U. delphinus some advantage against C. fluminea.